MEASUREMENT OF GEOMETRIC PARAMETERS OF THE FABRIC AND THE SPEED OF ITS MOVEMENT (Academia Science Repository, 2023)
When measuring such geometric dimensions of tissue segments as width and length, the requirements for absolute measurement accuracy carried out by a photoelectric device are significantly reduced. These dimensions are such that they do not fit in the field of view of the photodetector, therefore, methods based on the assumption that some part of the size to be measured is already known exactly and with the help of a photoelectric device it is only necessary to either count the number of such parts or measure a relatively small deviation from this known size. Indirect measurement methods are also used, based on the connection of the movement of the tissue with the rotation of the shafts or the movement of special mechanical elements that are engaged with the moving tissue and are in the field of view of the photodetector, with the help of which the indirect measurement is thus carried out.